Hydropower opportunities in Latin America and the Caribbean (2002)
Looks at aspects such as: hydropower development and potential; the new structure of the electric power sector, growth expectations; regional integration; environmental impact; and, the future of hydropower stations.
Keywords: HYDROELECTRIC POWER